Catalytic oxidation of glycerol in alkaline medium – Influence of mass transport limitations. (21st September 2022) - Namdeo, Ashutosh; Jhaveri, Jainesh H.; Mahajani, Sanjay M.; Suresh, Akkihebbal K.
Abstract: Glycerol upgradation via oxidation is characterized by a complex reaction network, further complicated by the heterogeneous (gas/liquid/solid) nature of the reaction. Thus, rates and selectivities could be significantly modified by transport limitations, especially in industrial reactors. In this work, we have studied the reaction on supported Pd and Au catalysts under alkaline conditions, both in the absence and presence of transport resistances, both external and internal. Reaction pathways proposed on the basis of data under kinetic control have been used to rationalize the findings. Interestingly and counterintuitively, the selectivity to C3 compounds is better under the influence of mass transfer. This behaviour is because of the nature of the reaction, which involves solution‐mediated reactions in addition to the metal‐catalyzed reactions on the catalyst surface. These findings have important implications for the scale up of this reaction and process design methodology. Abstract :